The effect of body mass index on the outcome of controlled ovarian hyperstimulation and intrauterine insemination in Hospital Sultan Ismail, Johor Bahru - Azmir, Nor Aida (2023)
OBJECTIVE To determine the effect of BMI on COH with IUI outcome in Hospital Sultan Ismail Johor Bahru, comparing the clinical pregnancy rate in normal and excessive BMI patients. The associated factors for successful outcomes among excessive BMI were determined. MATERIALS AND METHODS This 5-year retrospective study was performed in Hospital Sultan Ismail, Johor Bharu from 2016 until 2020. The data of 278 patients with 516 cycles, who underwent COH with IUI cycles were reviewed. Patients were categorized into those with normal BMI and excessive BMI, for which the treatment outcome was compared, using a chi-square test. Variables such as female age, duration of subfertility, cause of subfertility, and types of subfertility (primary and secondary), were analysed using regression tests to determine their associations in successful cycles among excessive weight patients. A p-value of <0.05 was taken as a significant difference. RESULTS A total of 516 IUI cycles were included in the analysis. Thirthy-eight percent of the cycle were in the normal BMI women, while 62% from excessive BMI (overweight and obese). Eighty-five-point three percent were ethnic Malay, 6.0% were Chinese, 4.7% were Indians, and 4.0% were other ethnicities, reflecting the normal Malaysian population. The means and standard deviations for normal BMI and excessive BMI were 21.9 kg/m2 and 29.1 kg/m2 respectively. The mean age for all subjects was 31 years old. The mean duration of subfertility in normal BMI was 65 months (5.4 years) and in excessive BMI was 62 months (5.2 years). A total of 49 pregnancies (9.4%) were achieved over 516 cycles. Out of this, 33 (67.3%) are from the excessive BMI group, and 16 (32.7%) are from the normal BMI group. There was no difference in the clinical pregnancy rate between normal BMI women and excessive BMI women women (adjusted OR 1.4, 95% CI 0.66 – 3.11, p-value 0.369). The difference in the ectopic pregnancy and miscarriage rates were also not significant. A negative correlation was found between female age and the success of COH IUI (p=0.815). Higher pregnancy rate was seen in secondary subfertility compared to primary subfertility (adjusted OR 2.8 (95% CI 0.97-7.92), p=0.058). The duration of infertility was found not significant in the outcome of COH IUI. In this result, all the causes of subfertility were negatively correlated with the successful COH IUI, possibly due to the small number involved. CONCLUSION In conclusion, our result contradicts the belief held by many that a higher BMI has a low success rate for COH IUI. The relationship between obesity and infertility outcomes is complex and can be influenced by multiple confounding factors. More studies and samples are necessary to evaluate the relationship between excessive BMI and successful of COH IUI.